PENANAMAN NILAI-NILAI AGAMA DALAM PENDIDIKAN ANAK DI ERA DIGITAL - Maulidiyah, Eka Cahya (IAIN Tulungagung, 2018)
The world experiences massive fundamental changes as a result of the digital era. Not only in the field of technology and communication, changes also occur in children's daily behavior. Various shows that are not good can be accessed easily by children and can cause negative behavioral effects on children. Supervision is needed from parents to guide children so that negative impacts can be minimized. The problem that occurs is that most parents are confused about what should be done to prepare children to face their environment. Planting religious values ​​from an early age is expected to be one of the strongholds of children facing change. This study aims to describe the cultivation of religious values ​​from an early age in a digital era filled with h extraordinary challenges through several strategies of planting religious values ​​such as understanding parents 'responsibilities, parents' commitment to children, and learning from the noblest example in Islam. The results of this study are expected to be one input for the world of children's education, especially in the family environment in preparing children in the digital era which is also referred to as the disruption era.